Choice and Variety-Seeking of E-liquids and Flavor Categories by New Zealand Smokers Using an Electronic Cigarette: A Longitudinal Study. Issue 5 (2nd December 2020) - Blank, Mei-Ling; Hoek, Janet
Abstract: Background: Little is currently known about how e-liquid flavor use evolves among electronic cigarette users. We describe patterns of e-liquid and flavor category use, and variety-seeking, among New Zealand adult smokers attempting to transition from smoking to e-cigarettes. Methods: Data were collected in 2018–19, using a longitudinal design comprising up to five in-depth interviews over a 12–20 week period. Participants ( n = 32) were current smokers aged ≥18 years, who were not currently using an e-cigarette once a week or more often, and were willing to use an e-cigarette in an attempt to stop smoking. We purchased participants a starter e-cigarette of their choice; they supplied their own e-liquids throughout the study. We extracted e-liquid use data from the verbatim interview transcripts, categorized these into flavor categories, and then explored these data for the whole sample, and by flavor category purchased at intake. Results: Most participants ( n = 12) selected a tobacco flavored e-liquid at intake; fruit ( n = 7), mint/menthol ( n = 6), and dessert/sweets and non-alcoholic beverage (both n = 5) were also popular. Most participants were still using their initially chosen flavor category at study exit, however, many described variety-seeking behaviors, which typically occurred during the first 12 weeks of enrolment. Conclusion: Most participants did not follow a straightforward e-liquid or flavor category pathway. Evidence of a variety-seeking continuum, typically occurring within the first 12 weeks, suggests possible opportunities at specialist e-cigarette stores to couple e-liquid purchasing occasions with cessation advice. Implications: Variety-seeking behavior was common and typically reported within the first 12 weeks of participants' e-cigarette-assisted attempt to transition away from smoking. Policies allowing diverse e-liquid flavors at specialist stores only could support users' variety-seeking and potentially create opportunities to couple e-liquid purchasing occasions with cessation advice during the first months of a transition attempt.